2019
DOI: 10.3389/fpsyg.2019.01202
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Pro-social Tendency of Left-Behind Adolescents in China: How Family Function and Self-Esteem Affect Pro-social Tendencies

Abstract: In China, adolescents are frequently left behind. To date, few studies have focused on the pro-social tendencies of left-behind adolescents and the relationship of family function, self-esteem, and pro-social tendency is yet to be examined. This study, therefore, aims to understand the status of pro-social tendency of left-behind adolescents and to explore the mediating and moderating roles of self-esteem in the relationship between family function and pro-social tendency. A large, school-based survey was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
3
8
0
2
Order By: Relevance
“…The current study showed that most of the adverse effect of negative life events on antisocial behavior tendencies is mediated by self-esteem. This result is consistent with the idea that self-esteem can be viewed as an important psychological resource and motivating factor for preventing antisocial behavior (Gao et al, 2019). Although it is impossible to change the negative life events that an individual has experienced, antisocial behavior tendencies can be avoided once self-esteem is improved, due to the negative effect of self-esteem on antisocial behavior tendencies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current study showed that most of the adverse effect of negative life events on antisocial behavior tendencies is mediated by self-esteem. This result is consistent with the idea that self-esteem can be viewed as an important psychological resource and motivating factor for preventing antisocial behavior (Gao et al, 2019). Although it is impossible to change the negative life events that an individual has experienced, antisocial behavior tendencies can be avoided once self-esteem is improved, due to the negative effect of self-esteem on antisocial behavior tendencies.…”
Section: Discussionsupporting
confidence: 88%
“…Antisocial behavior tendencies in adolescence, and its continuation in later life, are believed to involve an interaction of psychological vulnerability and environmental factors (Álvarez-García et al, 2019). Regarding psychological resources, self-esteem is thought to be an important internal resource, which has a significant effect in promoting children's development (Gao et al, 2019). Self-esteem is usually defined as an emotional evaluation of the individual himself/herself (Park et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Fear or anxiousness in peer situations is a necessary prerequisite for social anxiety according to DSM-5, as individuals in this situation fear being judged negatively by others ( Heimberg et al, 2014 ), causing impaired self-esteem. Previous studies have shown that left-behind children have lower self-esteem compared with non-left-behind children of the same age ( Dai & Chu, 2018 ), and lower self-esteem is associated with a greater impact of family functioning on their prosocial behavior ( Gao et al, 2019 ). In other words, left-behind children may show lower levels of self-esteem due to impaired family function, resulting in low prosocial behaviors, which in turn cause more pronounced social anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, el fomento de actitudes de respeto o compromiso en el alumnado universitario que realiza una labor social de servicio con colectivo migrante, y especialmente a través de la AF, podría ser un resultado destacable en el desarrollo social de jóvenes y especialmente en el plano cognitivo y de inclusión (Gao et al, 2019;Ruiz-Montero, Corral-Robles, García-Carmona, & Leiva-Olivencia, 2021). Por ello, debería ser una tarea obligatoria propiciar que los estudiantes universitarios comprendan el valor de la transmisión cultural y social que existe cuando hay interacciones sociales entre alumnado que realiza un servicio y los colectivos de personas migrantes que lo reciben (Capella-Peris, Gil-Gómez, & Chiva- Bartoll, 2019;Knight, Carlo, Mahrer, & Davis, 2016).…”
Section: Aprendizaje-servicio Como Un Instrumento De Desarrollo Compe...unclassified